Conflict Management Strategy to Enhance Student Discipline: Case Study at SMA Negeri 1 Kawali, Ciamis - Helmawati, Helmawati; Khendrayati, Rika; Rahayu, Noneng Sri; Risthiany, Ressy (Journal of English Language and Education, 2025)
Student indiscipline remains a persistent problem that undermines the creation of a productive and conducive learning environment. Repressive disciplinary measures have often failed to foster students' internal awareness and character development. This study investigates the potential of conflict management strategies as an alternative, educative, and participatory approach to improving student discipline. Employing a qualitative method with a case study design, the research was conducted at SMA Negeri 1 Kawali, Ciamis Regency. Informants included the principal, subject teachers, guidance and counselling teachers, students, and parents, all selected through purposive sampling. Data were collected through non-participatory observation, semi-structured in-depth interviews, and document analysis, and subsequently examined using Miles and Huberman's interactive model. The findings indicate that conflict management strategies, particularly those involving open communication, humanistic disciplinary approaches, and the reinforcement of teachers' roles as character educators, contributed to the development of discipline grounded in value awareness rather than mere formal compliance. Dialogical interventions, such as discussion forums and peer mediation, effectively reduced conflict escalation and enhanced students' sense of responsibility. Moreover, the role of teachers as moral exemplars and value facilitators was identified as a critical factor in shaping sustainable disciplinary behaviour. These findings suggest that humanistic and collaborative conflict management strategies play a significant role in fostering long-term character formation and responsible conduct among students